A Comprehensive Review on Nutritional Value, Medicinal Uses, and Processing of Banana. Issue 2 (17th February 2022) - Ranjha, Muhammad Modassar Ali Nawaz; Irfan, Shafeeqa; Nadeem, Muhammad; Mahmood, Shahid
ABSTRACT: Products from natural sources are being used from thousands of years. Banana is famous for its traditional, medicinal, and nutritional uses. It is rich in carbohydrates (22.84 g/100 g), provides energy about 370 kJ/100 g and it is considered to be one of the best sources of potassium (358 mg/100 g) that fulfils 8% of the daily recommended value. Along with the unique nutritional profile, banana possesses excellent medicinal properties. Banana is one of those fruits whose all parts could be processed, including its flesh and peel like banana chips, banana powder, banana biscuits, and most commonly banana juice.